2019
DOI: 10.1021/acs.est.8b07256
|View full text |Cite
|
Sign up to set email alerts
|

Branched Medium Chain Fatty Acids: Iso-Caproate Formation from Iso-Butyrate Broadens the Product Spectrum for Microbial Chain Elongation

Abstract: Chain elongation fermentation can be used to convert organic residues into biobased chemicals. This research aimed to develop a bioprocess for branched medium chain fatty acids (MCFAs) production. A long-term continuous reactor experiment showed that iso-caproate (4-methyl pentanoate, i-C6) can be produced via ethanol based chain elongation. The enriched microbiome formed iso-caproate from iso-butyrate at a rate of 44 ± 6 mmol C L–1 day–1 during the last phase. This amounted to 20% of all formed compounds base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 68 publications
4
45
2
Order By: Relevance
“…Interestingly, the large difference between the hydrolysis and acidification rates offers the possibility to avoid the degradation of amino acid and design the reactor such that they can be recovered. For instance, valine, leucine and iso-leucine are important substrates for branched fatty acids formation such as iso-butyrate, iso-valerate and iso-caproate that can be harvested from fermenting protein-rich waste streams for potential branched chain elongation [41].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the large difference between the hydrolysis and acidification rates offers the possibility to avoid the degradation of amino acid and design the reactor such that they can be recovered. For instance, valine, leucine and iso-leucine are important substrates for branched fatty acids formation such as iso-butyrate, iso-valerate and iso-caproate that can be harvested from fermenting protein-rich waste streams for potential branched chain elongation [41].…”
Section: Resultsmentioning
confidence: 99%
“…This fermenter community diversity strongly suggests that plenty of fermentative subproducts are available and indicates the occurrence of syntrophic associations. In fact, the Anaerolineae class may form syntrophic cooperation with methanogens ( Liang et al, 2015 ), which were also observed for UCG-001 ( de Leeuw et al, 2019 ). Similarly, Syntrophorhabdus , Syntrophus , and Smithella spp., from the Deltaproteobacteria class, and Caldisericum spp., from Caldisericia class, present in the same brown network, have demonstrated this syntrophic potential previously ( Mountfort et al, 1984 ; Guyot and Brauman, 1986 ; Liu et al, 1999 ; Qiu et al, 2008 ; Szafranek-Nakonieczna et al, 2019 ), although a direct interaction with Methanobacterium spp.…”
Section: Discussionmentioning
confidence: 61%
“…Currently, n -caproate is mainly produced from vegetable oils such as palm kernel oil [ 8 ], though it can be produced from more sustainable feedstocks such as agro-industrial waste by anaerobic fermentation and microbial chain elongation [ 9 , 10 ]. Compared to linear carboxylates, branched-chain carboxylates such as iso -butyrate are of special interest for alternative applications due to their different physical properties, including higher viscosity, higher oxidative stability, and a lower boiling point [ 11 ]. For example, iso -butyrate can be used for the synthesis of texanol, which is a widely used coalescent for latex paints [ 2 ].…”
Section: Introductionmentioning
confidence: 99%